Nasionalisme Sumber Daya Manusia Wirausaha dalam Pembangunan Bangsa - -, Rahmat (Unisia, 2016)
The problems are internal and extemal as scope of the Human Being Resources (MR) Included the Human Being Resources of Entrepreneur (HRE). As HR agent and objective in nation development process. Muhamad (2000:9) said that the human being influence in development to many problems like; planning, value sistem consideration and society. HRE prepare to everyting that become nationl problem. It is not only grow the economic sector but whatever the concerning nation development such as; confidence, skill at organizing, high level of energy, value of achievement over money, that support and keep stability all of nation development sector. The concerning about it, HRE probably seemb Inheren in ownself as the fenomena of characteristic HRE. Whereas, the role of HRE is as the important factor and certain in the economic field development. Therefopre, in totality national developmentall of society elements are needed to support stability such as; materiil, HR and included HRE. How do HRE comprehend the nationalism to or in national development? To analize this case, begin from the meaning of nationalism, the support factor bom ationalism/national identity, right and responsibility of society nationalism, characteristic of nationalism HRE, comprehension of nationalism HRE, implication of Islamic to comprehension of nationalism HRE, strategy of comprehension of nationalism HRE, and perspective view of comprehension of nationalism HRE. The result of study in this case viz; HRE have the characteristic that seemb to be examined theown personality become the civics that prepare to comprehend the nation identity/nationalism in nation development. The characteristic approach namely, life skill and life social skill. Dedication transformatiom HRE become mental character building.